PAME Work Plan 2009-2011. - Protection of the Arctic Marine Environment (PAME) (Protection of the Arctic Marine Environment (PAME), 2009)
Arctic Council working group Protection of the Arctic Marine Environment (PAME)s work plan for 2009-2011. Submitted to the Ministerial Meeting in Tromsø, Norway, April 29 2009.